Genetic Determinants of Gating Functions: Do We Get Closer to Understanding Schizophrenia Etiopathogenesis? - Rovný, Rastislav; Besterciová, Dominika; Riečanský, Igor (Frontiers in Psychiatry, 2020)
Deficits in the gating of sensory stimuli, i.e. the ability to suppress the processing of irrelevant sensory input, are considered to play an important role in the pathogenesis of several neuropsychiatric disorders, in particular schizophrenia. Gating is disrupted in schizophrenia patients but also their unaffected relatives, suggesting that gating efficiency may represent a biomarker associated with genetic liability to the disorder. To assess the strength of the evidence for the etiopathogenetic links between genetic variation, gating efficiency and schizophrenia, we carried out a systematic review of human genetic association studies of sensory gating (suppression of the P50 component of the auditory event-related brain potential) and sensorimotor gating (prepulse inhibition of the acoustic startle response). Sixty-nine full-text articles met eligibility criteria for inclusion in the review. In total 102 genetic variants were reported to be associated with gating functions: 32 variants for sensory gating, 66 variants for sensorimotor gating, and 4 variants for both sensory and sensorimotor gating. However, only 5 of these associations (4 for prepulse inhibition: CHRNA3 rs1317286, COMT rs4680, HTR2A rs6311, TCF4 rs9960767 and 1 for P50 suppression: CHRNA7 rs67158670) were consistently replicated in independent samples. Although these variants and genes were all implicated in schizophrenia in research studies, only 2 polymorphisms (HTR2A rs6311 and TCF4 rs9960767) were also reported to be associated with schizophrenia at a meta-analytic or genome-wide level of evidence. Thus, although gating is widely considered as an important endophenotype of schizophrenia, these findings demonstrate that evidence for a common genetic etiology of impaired gating functions and schizophrenia is yet unsatisfactory, warranting further studies in this field.